Artistic vs. popular elements in Paul Laric's novel Maribor remembered - Jerneja Petrič (Acta Neophilologica, 2012)
The article discusses Paul Laricʼs Maribor Remembered (1989) as a hybrid novel in terms of genre and artistic value. Essentially a detective novel, it also includes ethnic elements and humor as well as satire used to alleviate the growing tension as the elements of foul play multiply. Other elements, such as minute descriptions of Slovenian cuisine, or portrayal of Slovenian landscape further confirm the mixed-genre thesis.